Isolation of a Methanobrevibacter gottschalkii strain from an Eastern Gray Kangaroo - Volmer, James G.; Evans, Paul N.; Soo, Rochelle M.; Hugenholtz, Philip; Tyson, Gene W.; Morrison, Mark (Frontiers in Microbiology, 2024)
Methanogenic archaea inhabit the gastrointestinal tract of a variety of herbivores and humans, but the quantity (intensity) of methane emissions during feed digestion is variable.Macropodids such as the Eastern Grey Kangaroo (Macropus giganteus) are considered low methane-emitting animals but their gut methanogenic archaea have not been well characterized. The characterisation of methanogens from animals deemed to be low-methane emitters offers the potential to advance strategies and interventions that reduce livestock methane emissions.Here, we provide the characterization of a novel isolate of Methanobrevibacter gottschalkii, (strain EGK) which is the first Methanobrevibacter isolate from a marsupial host. Comparative analyses with other M. gottschalkii genomes confirmed a high degree of gene conservation, but there were also strain-level differences for gene counts involved in membrane transport, xenobiotics metabolism, nucleotide metabolism, and metabolism of cofactors and vitamins.Furthermore, the M. gottschalkii EGK genome is also remarkable for its multiple copies of large proviral elements, likely acquired through integration events unique to this strain. M. gottschalkii EGK is the first isolated representative of Methanobrevibacter from a low methane-emitting animal host, providing a useful reference genome to identify metabolic targets for methane mitigation.J.G.V., P.E., and M.M. designed the research. J.G.V. performed the research. J.G.V. wrote the paper. R.M.S., P.H. and M.M. provided a critical review of the manuscript. G.W.T. provided access to the high-performance computing and guidance in bioinformatic analyses. The author(s) read and approved the final manuscript.